Hull design and stability of catamaran for sport fishing applications / Muhammad Azwar Ikram Anwar Farid - Anwar Farid, Muhammad Azwar Ikram (2025)
This research investigates about the design and stability of catamaran for sport fishing applications, in order to address such crucial challenges like stability, safety, and sustainability in marine vessels. Traditional boats like monohull often bring issues in terms of pitching, rolling and poor stability in rough water conditions that can increase the safety risk and discomfort for anglers. The main objective is to build up an optimized catamaran hull design with better stability, hydrodynamics performance, and sustainability to ensure a safe and comfortable fishing platform.